Pay Your Fair Share? - An Empirical Analysis of Corporate Social Responsibility and Taxes - McGowan, Richard; Mahon, John F. (Journal of Management Policy and Practice, 2019)
This paper provides an empirical study of the relationship between Corporate Social Responsibility (CSR) perceptions and the effective taxes rates This study took data from over 2,600 firms (U.S. based, minimum market cap of $500 million). The data consisted of average effective tax rates (2010-2017), cash taxes paid from the same period, their 2017 ESG Score (converted from letter grade to number scale), their 2017 RepTrack score, their Fortune’s Most Admired Companies Ranking, and their 2017 Fortune Social Responsibility Peer Ranking.